2014
DOI: 10.1139/bcb-2014-0004
|View full text |Cite
|
Sign up to set email alerts
|

Myostatin inhibits proliferation and insulin-stimulated glucose uptake in mouse liver cells

Abstract: Although myostatin functions primarily as a negative regulator of skeletal muscle growth and development, accumulating biological and epidemiological evidence indicates an important contributing role in liver disease. In this study, we demonstrate that myostatin suppresses the proliferation of mouse Hepa-1c1c7 murine-derived liver cells (50%; p < 0.001) in part by reducing the expression of the cyclins and cyclin-dependent kinases that elicit G1-S phase transition of the cell cycle (p < 0.001). Furthermore, re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
12
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 48 publications
3
12
0
1
Order By: Relevance
“…SGLT2i is reportedly involved in reducing liver fat and ALT levels in patients with type 2 diabetes and non‐alcoholic fatty liver disease. Although the mechanistic details underlying the beneficial effects of SGLT2i on liver function have not been clarified, a preclinical study found deleterious effects of myostatin on hepatocytes, such as inhibition of proliferation and insulin‐stimulated glucose uptake. The present study confirmed that dapagliflozin reduced myostatin levels and improved γ‐GTP levels compared with control treatment in type 2 diabetes patients.…”
Section: Discussionsupporting
confidence: 80%
“…SGLT2i is reportedly involved in reducing liver fat and ALT levels in patients with type 2 diabetes and non‐alcoholic fatty liver disease. Although the mechanistic details underlying the beneficial effects of SGLT2i on liver function have not been clarified, a preclinical study found deleterious effects of myostatin on hepatocytes, such as inhibition of proliferation and insulin‐stimulated glucose uptake. The present study confirmed that dapagliflozin reduced myostatin levels and improved γ‐GTP levels compared with control treatment in type 2 diabetes patients.…”
Section: Discussionsupporting
confidence: 80%
“…Apart from this, they also found striking similarities between fhe-mir-2b-A and fhe-mir-2a-B and the two mir-27 orthologs, bta-mir-27a and bta-mir-27b, these two are known to target the 3′ un-translated region (UTR) of myostatin and insulin growth factor (IGF) in cattle and human (Miretti et al, 2013). While myostatin down-regulation has been associated with increased liver cell proliferation (Watts et al, 2014) and the decreased of has been associated with increased cancer risk (Loumaye et al, 2015). …”
Section: Mir In Trematodementioning
confidence: 99%
“…S1). Both are known to target the 3 0 untrans-171 lated region (UTR) of myostatin and insulin growth factor (IGF) 172 in cattle and human(Miretti et al, 2013), where myostatin down-173 regulation has been shown to increase liver cell proliferation 174(Watts et al, 2014) and the decrease of IGF -which is also targeted 175 by the highly expressed mir-190 orthologue -has been associated 176 with increased cancer risk(Arnaldez and Helman, 2012). Of the 177 total seven mir-2s in F. hepatica, these two miRNAs and their iso-178 forms show in total 11 conserved sites (in both datasets the highly 179 expressed fhe-mir-2c-B shows 13), that might allow the mir-27a/b 180 to target myostatin (Supplementary Fig.…”
mentioning
confidence: 99%